Population trends in achalasia diagnosis and management: a changing paradigm. Issue 5 (17th March 2021) - Trieu, Judy A; Dua, Arshish; Enofe, Ikponmwosa; Shastri, Nikhil; Venu, Mukund
Summary: The Chicago Classification of esophageal motility disorders improved the differentiation of achalasia subtypes and tailored treatment. Heller myotomy (HM) and pneumatic dilation are two established treatments for achalasia. Peroral endoscopic myotomy (POEM) has become a third definitive option and is on the rise. Using the National Inpatient Sample (NIS) database, we evaluated patients hospitalized with achalasia and associated surgical and endoscopic interventions from 2013 to 2017 and compared patients undergoing HM versus POEM. The NIS database was queried to include patients with achalasia. Patients who underwent HM, POEM (only 2017 due to lack of distinct procedure code in 2013), pneumatic dilation, or esophagectomy were identified. Adverse events during the hospitalization were also queried using diagnosis codes. From 2013 to 2017, patients hospitalized with achalasia increased from 16 850 to 19 485. There were reductions in the number of esophageal dilations (10.6–5.4%, P  < 0.001) and HM (18.7–13.1%, P  < 0.001). In 2017, 580 POEMs were performed. Compared with patients undergoing HM in 2017, patients who had POEM had higher mean age > 64 ( P  = 0.004), Charlson comorbidity index ( P  < 0.001), disease severity ( P  < 0.001), and likelihood of mortality ( P  < 0.001). There were no differences in length of stay, mortality, or total costs between the HM and POEM groups. Patients hospitalized with achlasia increased from 2013 to 2017, possibly due to the growth and accessibility of high-resolution esophageal manometry. As expertise in POEM increases, the number of POEM performed is anticipated to rise with possible further reductions in other treatment modalities for achalasia.